Eficiência e transparência na condução dos processos disciplinares das universidades federais - Fernandes, Ana Raquel Aires Ribeiro (2019)
The correctional structure of Higher Education Institutions provides adequate adjustments to the quality of the public service, through compliance with legal requirements and the execution of disciplinary processes. There is, however, a lack of studies that discuss and present proposals to make the management of disciplinary processes efficient and transparent. This paper intends to survey the conduct of disciplinary processes in the Brazilian Federal Universities, in the two dimensions previously mentioned and to carry out a comparative analysis to detect the best practices and, from them, to suggest a guide to improve the conduct of the processes. The diagnosis produced based on bibliographic research, an online survey of 31 of the 63 Brazilian Federal Universities and the analysis of contents of the disciplinary processes, produced in the first half of 2018 at the Federal University of Goiás; identified opportunities for improvement in the performance of the correctional sector of the Brazilian Federal Universities. Although 94% of respondents believe that the disciplinary process meets the correctional objective, both the quantitative and the qualitative study could be observed the slowness, bureaucracy, and lack of feedback for the involved in the conduct of these disciplinary proceedings. But it was also possible to identify the innovative practices that made it possible to construct a guidance itinerary to improve the efficiency and transparency of disciplinary processes in the IFES.